THE EFFECT OF PERSONALITY AND WORK FATIGUE ON ORGANIZATIONAL COMMITMENT AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE IN THE MAJALENGKA DISTRICT GOVERNMENT - Della Sopyani Agustin; Kartono (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence of personality and work fatigue on organizational commitment and its implications for employee performance in the Majalengka Regency Government. The approach used is quantitative with Casual Associative, through data collection using questionnaires distributed to employees as respondents. Data were analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results of the study indicate that personality has a significant effect on organizational commitment and employee performance. Work fatigue (burnout) has a significant effect on organizational commitment and employee performance. In addition, organizational commitment is proven to play a role as a mediating variable in the relationship between personality and work fatigue on employee performance. These findings confirm that personality factors and the level of work fatigue have an important role in shaping organizational commitment that has an impact on improving employee performance. This study concludes that human resource management that considers personality aspects and controls work fatigue can strengthen organizational commitment and improve employee performance. Future research is recommended to add other contextual variables to enrich the research model.